From brittle to elastic: substituent effects on mechanical flexibility in aromatic amide crystals - Bhowmik, Aritra; Das, Nirmal; Saxena, Ashish Kumar; Mishra, Kamini; Barsu, Nagaraju; Mishra, Manish Kumar (Chemistry-An Asian Journal, 2026)
Mechanical flexibility in molecular crystalline materials represents a compelling paradigm shift from the long-held perception of crystals as inherently brittle solids. Herein, we demonstrate a brittle-to-elastic transition by subtle molecular modification in a pair of structurally analogous aromatic amides; N-[(4-methoxyphenyl)methyl]formamide (N4MFA, Crystal 1) and N-benzylformamide (NBFA, Crystal 2). Despite their close structural similarity, Crystal 1 exhibits brittle fracture under minimal stress, whereas Crystal 2 shows 1D elastic flexibility with reversible bending. Structural, computational, and mechanical analyses reveal that this contrast arises from substituent-controlled supramolecular packing. In Crystal 1, the methoxy (-OCH3) group promotes dense, anisotropic packing, leading to rigidity and fracture under stress. Removing the substituent in Crystal 2 enhances isotropy, pi-pi stacking, and interlocked packing, enabling reversible strain during elastic bending. Nanoindentation, energy framework, and elastic tensor analyses confirm this transition: Crystal 2 shows near-isotropic stiffness (E max/E min = 1.65) and interconnected energy networks, whereas Crystal 1 exhibits pronounced anisotropy (E max/E min = 3.95) and 1D cohesion. Hirshfeld surface analysis supports more balanced contacts in the elastic crystal. This work establishes a direct structure-mechanical correlation, showing that minor chemical modifications can tune flexibility and provide insights to guide the development of adaptive crystalline materials.
Keywords: crystal engineering; Elasticity; Mechanical property; nanoindentation; responsive crystals

Phosphine radical cation catalysis for Markovnikov hydroamination of unactivated alkenes - Das, Nirmal; Barsu, Nagaraju (Journal of Chemical Sciences, 2026)
Markovnikov-selective hydroamination of unactivated terminal alkenes has long remained a challenging transformation in C-N bond formation. Fan and co-workers1 addressed this using a metal-free phosphine photoredox system that operates via an unprecedented phosphine radical cation (P(IV)) mechanism, enabling alkene activation toward azole addition. This work highlights a powerful new strategy for C(sp3)-N bond construction beyond traditional transition-metal catalysis.Graphical abstractMetal-free phosphine photoredox catalysis enables Markovnikov-selective hydroamination of unactivated terminalalkenes via a novel phosphine radical cation mechanism, off ering a new strategy for C(sp3)-N bond formation.
Keywords: azoles; hydroamination; Markovnikov selectivity; Phosphine catalysis; photoredox; radical cation